2013
DOI: 10.1111/cen.12086
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone binding globulin and insulin resistance

Abstract: SummarySex hormone binding globulin (SHBG) is a glycoprotein composed of two 373-amino-acid subunits. The SHBG gene and a promotor region have been identified. The SHBG receptor has yet to be cloned but is known to act through a G-protein-linked second-messenger system following plasma membrane binding. The principal function of SHBG has traditionally been considered to be that of a transport protein for sex steroids, regulating circulating concentrations of free (unbound) hormones and their transport to targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(169 citation statements)
references
References 77 publications
10
155
4
Order By: Relevance
“…In addition, testosterone therapy decreases SHBG. SHBG may have biological actions that improve glucose metabolism (Wallace et al 2013). Future studies should clarify whether effects of testosterone on adiponectin, SHBG and other potential regulators of glucose metabolism, such as undercarboxylated osteocalcin (Yeap 2011), may limit testosterone therapy-mediated improvements in glucose metabolism.…”
Section: Effect On Lipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, testosterone therapy decreases SHBG. SHBG may have biological actions that improve glucose metabolism (Wallace et al 2013). Future studies should clarify whether effects of testosterone on adiponectin, SHBG and other potential regulators of glucose metabolism, such as undercarboxylated osteocalcin (Yeap 2011), may limit testosterone therapy-mediated improvements in glucose metabolism.…”
Section: Effect On Lipidsmentioning
confidence: 99%
“…This is because of the confounding effects of SHBG, itself being a strong associate of insulin resistance (Wallace et al 2013). In a study from the Framingham cohort, SHBG but not testosterone was prospectively and independently associated with incident metabolic syndrome (Bhasin et al 2011a).…”
Section: End Organ Deficits Of Androgen Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…This can be added up to the adverse action caused by the increase of body mass index, as previously stated [1]. Several researches have proved a negative correlation between SHBG levels and insulin sensitivity [5]. In addition, most prospective studies support the role of reduced SHBG levels as a possible predictive factor of DM2 development [6].…”
Section: Unconventional Physiopathological Characteristicsmentioning
confidence: 79%
“…SHBG is a protective factor, and a low level of SHBG might serve as a critical factor during the pathogenesis of PCOS and MetS [27]. Several sources of evidence have shown that decreased SHBG is associated with MetS and IR in women with PCOS [28][29][30][31][32]. Therefore, paternal history aggravates the metabolic disturbance in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%